Prevalence of Behavioral and Psychological Symptoms in Patients With Cognitive Decline Before and During the COVID-19 Pandemic - Kuroda, Yujiro; Sugimoto, Taiki; Matsumoto, Nanae; Uchida, Kazuaki; Kishino, Yoshinobu; Suemoto, Claudia Kimie; Sakurai, Takashi (Frontiers in Psychiatry, 2022)
Objective: Preventive measures to limit the spread of COVID-19 are essential, but often cause social isolation, affecting the physical and mental health of older adults. Patients with dementia are likely to have worsening behavioral and psychological symptoms of dementia (BPSD) owing to pandemic restrictions. To examine this, we described BPSD before and during the COVID-19 pandemic. Methods: We identified patients at a memory clinic in Japan between October 2018 and December 2019 (15 months before the pandemic began, n = 1384) and between April 2020 and June 2021 (15 months after the State of Emergency was declared; n = 675 patients). A propensity score was used to match 576 patients from each group. The Mini-Mental State Exam was used to classify cognitive function into mild and moderate/severe. Dementia Behavioral Disturbance Scale was used to evaluate BPSD. The association between BPSD before and during the pandemic was evaluated using binomial logistic regression models. Results: The levels of frequent night waking were higher in individuals before the pandemic than in those evaluated during the pandemic in both the mild group (adjusted odds ratio [AOR] = 1.82, 95% CI 1.02-3.23) and the moderate/severe group (AOR = 1.96, 95% CI 1.19-3.23) . During the pandemic, physical attacks were higher in the mild group (AOR = 4.25, 95% CI 1.12-16.07), while night wandering was higher in the moderate/severe group (AOR = 2.22, 95% CI 1.03-4.81). Conclusion: In patients with cognitive impairment, some BPSD were more prevalent during the pandemic, depending on dementia severity. The findings pertaining to the higher frequency of sleep disturbance and aggressiveness during COVID-19 should be used to guide BPSD screening in patients with dementia and to provide evidence-based interventions.